Hybrid modular multilevel converter (MMC) applications under over-modulation - Donoso Merlet, Felipe Octavio (2022)
The Modular Multilevel Converter (MMC) has become a prominent converter topology due to its several advantages: high modularity, high scalability, low harmonic distortion, and high efficiency. In particular, due to its modular structure, it is possible to increase its voltage rating by stacking extra cells. The MMC has been successfully applied to high voltage direct current (HVDC) transmission systems and drive applications.